2008
DOI: 10.1253/circj.cj-08-0010
|View full text |Cite
|
Sign up to set email alerts
|

One-Year Clinical Outcomes of Dialysis Patients After Implantation With Sirolimus-Eluting Coronary Stents

Abstract: ialysis patients show a complex morphology of coronary artery lesions, especially marked calcification, 1 and are at higher risk for target lesion revascularization (TLR) after coronary stenting than nondialysis patients. 2 Utilization of stenting and debulking techniques reportedly improves immediate and long-term outcomes after percutaneous coronary intervention (PCI) in patients with calcified and complex lesions. [2][3][4] Recently, the use of a sirolimus-eluting stent (SES; Cypher, Cordis, Johnson & Johns… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
1

Year Published

2009
2009
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 21 publications
1
23
1
Order By: Relevance
“…The availability of DES has been shown to significantly reduce clinical and angiographic restenosis in patients with preserved, as well as impaired, baseline renal function. [35][36][37][38] Despite that finding, in our study the use of DES did not offer an incremental benefit in the rates of death, MI or CVE, and was still associated with a higher risk of repeat revascularization in the 3-vessel population, as compared with CABG. However, the rate of follow-up angiography in the DES group was significantly higher than in the CABG group (39.0% vs 13.9%, P=0.000), so the rate of asymptomatic graft stenosis or occlusion may have been dramatically underestimated in the CABG group relative to the DES group.…”
Section: Discussioncontrasting
confidence: 79%
“…The availability of DES has been shown to significantly reduce clinical and angiographic restenosis in patients with preserved, as well as impaired, baseline renal function. [35][36][37][38] Despite that finding, in our study the use of DES did not offer an incremental benefit in the rates of death, MI or CVE, and was still associated with a higher risk of repeat revascularization in the 3-vessel population, as compared with CABG. However, the rate of follow-up angiography in the DES group was significantly higher than in the CABG group (39.0% vs 13.9%, P=0.000), so the rate of asymptomatic graft stenosis or occlusion may have been dramatically underestimated in the CABG group relative to the DES group.…”
Section: Discussioncontrasting
confidence: 79%
“…[16][17][18] However, recent reports from Japan have shown that the TLR rate is similar between SES and BMS groups of dialysis patients. 11,19,20 As discussed in those reports, a higher rate of angiographic follow-up may explain the increasing rate of TLR in Japan. Furthermore, different percentages of patients with complex and highly calcified lesions may contribute to the relatively high rate of TLR.…”
Section: Discussionmentioning
confidence: 84%
“…11 Coronary plaques in dialysis patients are characterized by increased medial thickness and marked calcification, which are potential risks for suboptimal stent expansion. 12 According to IVUS analysis, under-expansion seems to be the most common mechanism of SES restenosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have suggested that dialysis is a major risk factor for restenosis after DES implantation, although the rates of restenosis are relatively lower than those of BMS. [20][21][22][23][24] There have been several reports suggesting differences in the properties of calcification between the dialysis patients and the non-dialysis patients. First, it has been reported that arterial calcification can be divided into intimal calcification, and medial calcification.…”
Section: Dialysis Patientsmentioning
confidence: 99%